“An Ordinance to Prohibit the Carrying of Concealed Deadly Weapons.” St. Helena Star, December 9, 1884, p. 2. Volume 11, Number 23 - (:unkn) unknown (General Publisher, 1884)
Prohibited the concealed carry of any pistol, dirk, sword, slung-shot, or other dangerous or deadly weapon. Violators fined not less than ten nor more than fifty dollars or imprisoned not less than one day nor more than thirty days.
--
Keywords: CARRY - CONCEALED